Heeding Cassandra: The Neutered Mother, the Sexual Family, and Other Twentieth Century Tragedies - Vagelatos, John (Columbia Journal of Gender and Law, 1995)
Cassandra, the daughter of King Priam and Queen Hecuba of Troy, was so beautiful that in an attempt to woo her, the God Apollo granted her the gift of vision to foresee the future. However, when she spurned his sexual advances, he cursed her in turn, so that no one would ever believe in her visions or heed her warnings. Consequently, although she foresaw the fall of Troy, she was powerless to prevent it. The character of Cassandra resounds powerfully for feminist visionaries. Cassandra was the product of a patriarchal culture which privileged the voices of her brothers and fathers. She benefitted from her class, but was separated by her gender. She was granted a powerful alternative vision, but could not convince the male power structure to acknowledge it. The royal patriarchy’s disbelief of and failure to listen to Cassandra’s prophecies led to its own destruction. In her latest work The Neutered Mother, the Sexual Family and other Twentieth Century Tragedies (“The Neutered Mother”), Martha Albertson Fineman’ confronts Cassandra’s dilemma. She conceptualizes an alternative vision of the family, while acknowledging the difficulty in making people hear, understand, and heed her message. In The Neutered Mother, Professor Fineman proposes the legal abolition of marriage and a reconceptualization of our basic understanding of the family. Linked with images of neutered mothers and sexual families, her theories are sure to jar traditional sensibilities, but Fineman settles for nothing short of the extreme. She brings to us a fresh perspective, attempting to break away from even “core” feminist perspectives. Fineman sees the family as the key construct by which patriarchy has continually reproduced itself. However, she does not accept current limited conceptions of the family as an ideological institution. She argues that our basic understanding of the family limits both what change can be accomplished within that unit, and what feminist goals can be achieved in society. Rather than seeking to redefine gendered relations within the construct of the family (a historical goal of feminist legalists), and therefore be coopted by the limits of the model, Martha Fineman unravels the institution and weaves an alternative norm. She exposes the basic unit of the traditional model: the horizontal sexual relationship between husband and wife. By stepping outside of the traditional model, she is able to reveal the various threads which tightly tie together to keep the model intact: governmental attacks on single motherhood, the rise of father’s rights discourse, and the failure of the egalitarian family. She is also able to locate the Gordian knot: the inherent inability of current family conceptions to adequately address dependency or gender equality. Ultimately, however, Fineman is aware of the limits of her power to reweave the family unit into a new fabric, and we are forced to examine the utility of her formulations.